Guidelines for the use of social media in the university libraries of the Catarinian Association of Educational Associations - Catoni Custódio Maciel, Camila Emilia (2019)
Investigates the presence of guidelines for the use of social media in academic libraries of the ACAFE system. It presents the quantitative of university libraries that are present in social media and analyzes the social media that are most used by these informational units. The research is exploratory, adopts a qualitative approach through documentary and bibliographic research, its universe is composed of 16 universities of the ACAFE system and its corpus involves the websites of the universities and their institutional documents, and the respective academic libraries. It can be seen that the manuals for the use of recovered social media are institutional, that is, created by universities, and none of the 56 libraries (central and sectoral) researched have their own document. The presence of libraries in social media can be seen, with Facebook being the most used digital social network, where 30 of the 56 academic libraries have a fanpage and 1 uses a profile, in contrast the other medias analyzed are little explored. It is concluded that the presence in the social media can contribute to expand the library to a space of experience, creativity and active participation of the community. The creation of guidelines for the use of media is essential, as good practices for the good performance and achievement of the desired results.